Factors associated with offering HIV testing to people aged ≥ 50 years: A qualitative study. (March 2022) - Youssef, Elaney; Wright, Juliet; A Davies, Kevin; Delpech, Valerie; Brown, Alison; Cooper, Vanessa; Sachikonye, Memory; de Visser, Richard
Background: Individuals aged ≥ 50 years continue to be disproportionately affected by late HIV diagnosis, which is associated with poorer health outcomes and onward transmission. Despite HIV testing guidelines and high acceptability of HIV testing among all patients, clinicians are less likely to offer a test to an older individual. The aim of this study was to identify clinician-related factors associated with offering HIV testing to patients aged ≥ 50 years. Methods: Twenty clinicians who had been involved in the care of an older patient diagnosed late with HIV were interviewed. Results: Thematic analysis identified seven factors associated with offering HIV testing to older people: knowledge, stigma, stereotyping and perception of risk, symptom attribution, discussing HIV with patients, consent procedures and practical issues. Conclusions: Although some factors are not unique to older patients, some are unique to this group. Many clinicians lack up-to-date HIV-related knowledge, feel anxious discussing HIV with older patients and perceive asexuality in older age. In order to increase the offer of HIV testing to this group, we identified clinician-related barriers to test offer that need to be addressed.